INFECTIOUS MONONUCLEOSIS AND ITS CLINICAL VARIABILITY: A CASE REPORT (CIPEEX, 2022)
INFECTIOUS MONONUCLEOSIS (MI) IS AN INFECTIOUS DISEASE CAUSED BY THE EPSTEIN-BARR VIRUS (EBV) BELONGING TO THE HERPES GROUP. THE OBJECTIVE OF THIS STUDY WAS TO REPORT A CLINICAL PICTURE RELATED TO INFECTIOUS MONONUCLEOSIS. A FEMALE PATIENT, 18 YEARS OLD, WAS ATTENDED BY A MEDICAL PROFESSIONAL COMPLAINING OF ASTHENIA, DYSPNEA AND ODYNOPHAGIA. PHYSICAL EXAM SHOWED PHARYNGITIS WITH GRAYISH WHITE TONSIL EXUDATE. AFTER THE ERRONEOUS DIAGNOSIS OF BACTERIAL TONSILLITIS, ORAL ANTIBIOTIC THERAPY WITH AMOXICILLIN WAS INITIATED. TWELVE HOURS AFTER THE INTRODUCTION OF AMOXICILLIN, THE PATIENT PRESENTED DIFFUSE ERYTHEMATOUS SPOTS ON THE FACE AND CHEST. ON THE FOLLOWING DAY AFTER THE START OF THE ANTIBIOTIC USE, HE SOUGHT FIRST AID IN A TERTIARY HOSPITAL AND LABORATORY TESTS DID NOT SHOW CHANGES, EXCEPT FOR A RISE IN C-REACTIVE PROTEIN WITH A CONCENTRATION OF 12.1 MG/L. RECEIVED THE DIAGNOSIS OF ALLERGIC REACTION TO THE USE OF THE ANTIBIOTIC. DIPYRONE WAS ADMINISTERED INTRAVENOUSLY, INTRAMUSCULARLY PROMETHAZINE AND ORAL HYDROXYZINE EVERY 8 HOURS AND AMOXICILLIN WAS REPLACED WITH ORAL LEVOFLOXACIN. THE NEXT DAY THE PATIENT EVOLVED WITH CRANIOCAUDAL RASH ONSET, PERSISTENCE OF TONSILLAR HYPERTROPHY, ODYNOPHAGIA AND DYSPHAGIA TO SOLID FOODS. HE RETURNED TO THE EMERGENCY ROOM AT THE SAME HOSPITAL THE NEXT DAY. DURING THE VISIT, THE DIAGNOSIS OF THE CONDITION WAS COMPATIBLE WITH THE ADVERSE REACTION TO THE USE OF THE PRESCRIBED ANTIBIOTICS. INITIATED TREATMENT WITH HYDROCORTISONE AND INTRAVENOUS RANITIDINE. LEVOFLOXACIN WAS REPLACED BY SULFAMETHOXAZOLE / TRIMETHOPRIM, ALONG WITH THE PRESCRIPTION OF ORAL PREDNISOLONE. HYDROXYZINE WAS MAINTAINED. SEROLOGICAL TESTS SHOWED SEROLOGICAL ASSAYS OF IGG AND IGM REAGENTS FOR EPSTEIN-BARR, WITH CONCENTRATIONS OF 3.47 AND 34 S / CO, RESPECTIVELY. AFTER CONCLUDING THE DIAGNOSIS OF MI, THE PROCEDURE WAS THE SUSPENSION OF LEVOCETIRIZINE ANTIBIOTIC THERAPY, AS WELL AS THE MAINTENANCE OF PREDNISOLONE AT THE PATIENT'S DISCRETION TO RELIEVE PRURITUS. AFTER 3 WEEKS THERE WAS COMPLETE REGRESSION OF THE RASH. WHILE THE DISCOMFORT, DYSPNEA AND TONSILLAR HYPERTROPHY RESOLVED IN THE FIRST ONE AFTER THE DIAGNOSIS OF MI. THE MI HAS A DIAGNOSIS OF MEDIUM COMPLEXITY, CONSIDERING THAT IT HAS VARIABLE CLINICAL FORMS. THUS, A CLINICAL HISTORY AND A DETAILED PHYSICAL EXAMINATION ARE IMPORTANT TO AVOID DIAGNOSTIC ERRORS.
Keywords: Infectious Mononucleosis, Rash, Amoxicillin, Epstein-Barr Virus Infections.